Kualitas Pelayanan Trainee Dalam Memberikan Pelayanan di Restoran Speakizzie Hotel Pulang ke Uttara Pasca Covid-19 Quality of "Trainee" Services in Providing Services at The Speakizzie Hotel Restaurant Pulang ke Uttara Post Covid-19 - Aulia, Gea Indah; Lasally, Adesty (EBBANK, 2024)
The Special Region of Yogyakarta is a major tourist destination with various facilities and infrastructure such as star and non-star hotel accommodation (Murti,2017).  However, from 2018 to 2021, there was no increase in hotel growth each year. Tourism activities are very dependent on the presence of human resources, as drivers of tourism industry activities including hotels, so the realization of tourism activities is marked by the interaction between consumers who are on tour and producers as parties offering tourism products or services. Based on the background above, researchers conducted research with the title “Service Quality of Trainees at Speakizzie, Pulang ke Uttara Hotel after Pandemic Covid-19”. This Type of research data was collected using interview techniques, observation, literature study, and documentation. The data analysis technique used is descriptive. The results of the research show that trainees at  Speakizzie, Pulang ke Uttara Hotel, have service quality indicators, 1) Reliability is quite good, 2) Responsiveness is quite good, 3) Assurance is quite good, 4) Empathy is quite good, 5) Direct evidence (tangibles) is quite good.